Environmentally Friendly Agricultural Development - Mas Teddy Sutriadi; A. Wihardjaka; E. Srihayu Harsanti; Ali Pramono (Indonesian Center for Agriculture Land Resource Development, 2021)
Abstract. Environmentally friendly agriculture is an agricultural system that manages all resources and inputs of the agricultural system to achieve optimal productivity and economic benefits, but has a low risk of resource and environmental sustainability, as well as global warming/climate change. Environmentally friendly implementation strategies lead to synergy and integration between technologies, optimization of resources and production inputs which are carried out through three approaches, namely: (1) Anticipation, adaptation, and mitigation approaches in the context of global warming and climate change, (2) Mitigation approach, countermeasures, and remediation in the context of edhapik and biological environments, and (3) Land remediation approach in the context of degradation and pollution of land, air and ecosystem resources due to excessive use of agrochemicals. Support for research activities and development of adaptation, mitigation and remediation strategies for the restoration of polluted land is expected to increase the economy while producing healthy agricultural products and environment. Various regulations and policies for implementing a sustainable agricultural environment, socialization and implementation in the field must be supported by an agricultural environment information system that is easily accessed by users.